Everyone here is lying : a novel [compact disc, unabridged] - Lapena, Shari, 1960- (Penguin Audio, 2023)
William Wooler is a family man, on the surface. But he's been having an affair, an affair that ended horribly this afternoon at a motel up the road. So when he returns to his house, devastated and angry, to find his difficult nine-year-old daughter, Avery, unexpectedly home from school, William loses his temper. Hours later, Avery's family declares her missing. Suddenly Stanhope doesn't feel so safe. And William isn't the only one on his street who's hiding a lie. As witnesses come forward with information that may or may not be true, Avery's neighbors become increasingly unhinged. Who took Avery Wooler?